An assessment of government policy response to HIV/AIDS in Ghana - Julius Fobil (SAHARA-J, 2006)
The HIV/AIDS epidemic in Africa has assumed a dimension raising heartbreaking anxiety among national governments and civil society groups. In Ghana for example, the pandemic is well-documented and has gone beyond a health problem, and now encompasses all socio-economic aspects of life. The estimated rate of infection from the mid-1980s to 2000 has more than doubled, and in spite of the control efforts by various groups and organisations, prevalence of the disease has not declined notably. This paper assesses government policy, programmes and strategies to combat the disease, using analysis of time trend sentinel data and weighting these against control efforts. The assessment revealed that 380 000 adults and 36 000 children are currently infected. There are wide spatial variations in prevalence across the country and the overall national prevalence has fluctuated over time, standing at 2.6% in 2000, 3.6% in 2002 and 3.1% in 2004. This appears relatively lower than in adjacent countries, where prevalence is around 5% and over 25% in East and Southern African countries.Although the review found a robust multipronged government intervention approach to containing the disease, we are hesitant to claim that the fairly stable or low national prevalence in Ghana compared with its immediate neighbours may have been the consequence of the effectiveness of national AIDS control programmes and impact of government interventions.